2007
DOI: 10.1016/j.pbb.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-1-(4-methoxyphenyl)-2-aminopropane (PMMA) and N-Methyl-1-(3,4-methylenedioxyphenyl)-2-aminopropane (MDMA) produce non-identical discriminative stimuli in rats

Abstract: N-Methyl-1-(3,4-methylenedioxyphenyl)-2-aminopropane (methylenedioxymethamphetamine, MDMA, Ecstasy) and its structurally abbreviated congener N-methyl-1-(4-methoxyphenyl)-2-aminopropane (para-methoxymethamphetamine, PMMA) are chemically related designer drugs, and PMMA is sometimes sold on the clandestine market as a substitute for MDMA. Prior drug discrimination studies have found that MDMA and PMMA substitute for one another suggesting that they produce similar discriminative stimulus effects in rats. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In drug discrimination studies, MDMA showed generalization in PMMA-trained rats and partial generalization in S(+)amphetamine-trained rats, but is not recognized by DOM-trained rats. This suggests that MDMA is primarily an empathogen with some stimulant-like effects, but it is not a hallucinogenic agent (Glennon 1991;Glennon et al 2007;Oberlender and Nichols 1988). These observations correlate well with subjective effects previously described in humans, where MDMA was reported as a distinctive entity from hallucinogens and "pure" stimulants (O berlender and Nichols 1988).…”
Section: Brief Overview Of Amphetamines and Cathinonessupporting
confidence: 86%
“…In drug discrimination studies, MDMA showed generalization in PMMA-trained rats and partial generalization in S(+)amphetamine-trained rats, but is not recognized by DOM-trained rats. This suggests that MDMA is primarily an empathogen with some stimulant-like effects, but it is not a hallucinogenic agent (Glennon 1991;Glennon et al 2007;Oberlender and Nichols 1988). These observations correlate well with subjective effects previously described in humans, where MDMA was reported as a distinctive entity from hallucinogens and "pure" stimulants (O berlender and Nichols 1988).…”
Section: Brief Overview Of Amphetamines and Cathinonessupporting
confidence: 86%
“…Drug discrimination studies in rats showed racemic m -methoxyamphetamine ( 5 ) to produce amphetamine-like effect and to generalize to ( S )- 1 38 but not to DOM ( 8 ); examination of the individual enantiomers of 5 in drug discrimination studies showed significantly reduced response rates and disruption of behavior by both enantiomers. 39 Relatively high potency at h TAAR1 has also been found for ( S )- 2,5-dimethoxy-4-ethylamphetamine (( S )- 9 ), again suggesting that it may produce amphetaminelike effects. The literature data for racemic ( S )- 9 imply some anxiogenic effects in humans at low dose (25 mg); 37 but no clear-cut amphetamine-like stimuli of either of the individual enantiomers or of the racemate were detected in a study in which human subjects were given oral doses of 1–4 mg of 9 .…”
Section: Discussionmentioning
confidence: 96%
“…The amphetamine-derivatives MBDB, 4-MA, MDEA, 4-MTA, PMA, and PMMA show uptake inhibition profiles and DAT/SERT ratios similar to MDMA (Table 1). In vivo drug discrimination experiments in rats suggest that PMA, PMMA and 4-MTA show MDMAlike properties (Dukat et al 2002;Glennon et al 2007). However, these substances did not substitute for amphetamine in the drug discrimination experiments, which predicts that PMA, PMMA and 4-MTA have less stimulant-like properties than MDMA.…”
Section: Mdma-like Amphetamine Derivativesmentioning
confidence: 95%